THE CONTENT OF FORMING READING COMPREHENSION SKILLS IN PRIMARY STUDENTS - Abdijamilova Mahfuza Makhmudovna; Yusupbayeva Lobar Alisher kizi (Scholar Express Journals, 2025)
This article discusses the issues of the content of developing reading comprehension skills in primary school students
Keywords: Knowledge; skills and competence; reading text